PENGARUH KESADARAN, PENGETAHUAN DAN PEMAHAMAN, SANKSI PERPAJAKAN DAN PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK NOTARIS DI KOTA SEMARANG - Anggia Cahyaning Wibiyani; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2019)
This study aims to analyze the effect of tax awareness, knowledge and understanding of taxation, taxation sanctions and tax authorities services on Notary taxpayer compliance in Semarang City. This study consists of four independent variables and one dependent variable. The independent variables in this study are awareness of taxation, knowledge and understanding of taxation, taxation sanctions and tax authorities services. The dependent variable in this study is taxpayer compliance. The population of this study is a notary taxpayer in the city of Semarang. Samples using convenience sampling is 76 respondents. The techniques of data collection were done by using questionnaire. Analysis of research data using multiple linear analysis with SPSS 25.0 program. The results of this study indicate that tax awareness, knowledge and understanding of taxation have a significant positive effect on taxpayer compliance, but tax sanctions and tax authorities do not significantly influence taxpayer compliance